Global Board Market Index Shariah: A Comprehensive Analysis of the 2020-2023 Trends - Akbar, Aldi; Kartawinata, Budi Rustandi; Hidayat, Agus Maolana (PT. Riset Press International, 2024)
Global stock markets experienced several spikes and dips during the pandemic. In March 2020, there was a sharp decline in many stock exchanges around the world, known as